Metaphoric meanings of words denoting animals in English and Vietnamese - Ut, Huynh Thi (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
Animals are considered very important and significant to human life. Human tends to express different emotions and behaviors with the help of animals. However, people who speak English, and people who speak Vietnamese have different ideas for the same animals. This research deals with the metaphoric meanings denoting animals in English and Vietnamese. It aimed to find out the similarities and differences between the two languages. The research data were collected from many dictionaries and books of languages, idioms, proverbs, and metaphors. They were then described and analyzed on the metaphoric meanings under qualitative and quantitative approaches.